(3eLehY COHjs - (3eLghds
(3ChdgG (B:s
(3bGd HYV GdeZGQHI jJThb Edi GdbjQhGf, hbjd gh GdoMUQj(B: (3aj cd jhe eY GdCMHGH dPGoJ adjS aj GdYjT eSQhQkG EPG aGJhG s
(3BNQgG (B:s
(3QabkG HbdHj aCfJ SGcfg hGQMe NVhYj abO Vfi LSOj s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GdfSNI HgG VHWs
(3jTJed Ydi bUGFO hebWYGJ dHYV GdTYQGAs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs